Air transportation and the COVID-19 pandemic: Towards a change of the path in the spanish airport network? - Díez-Pisonero, Roberto; Gago-García, Cándida (Revista de Estudios Andaluces, 2022)
COVID-19 has been a profound shock to the global economy and, in particular, in the aviation industry, as it is affected by restrictive measures to stop the spread of the virus. Besides describing the impact of the pandemic on the commercial aviation sector globally, this study analyses the air connectivity of Spanish airports in order to understand the changes that have occurred in the country’s airport network because of COVID-19. Through the study of connectivity with a topological connectivity coefficient and its mapping, this analysis looks at the history of the Spanish aviation diachronically (1970 to 2020). There is no doubt that the pandemic is affecting aviation in away never experienced before, both in terms of commercial (frequencies and routes) and health security.